Update on cancer and central nervous system tumor surveillance in pediatric NF2-, SMARCB1-, and LZTR1-related Schwannomatosis - Perrino, Melissa; Jongmans, Marjolijn C.J.; Tomlinson, Gail E.; Greer, Mary-Louise C.; Scollon, Sarah R.; Mitchell, Sarah G.; Hansford, Jordan R.; Schultz, Kris Ann P.; Kohlmann, Wendy K.; Kalish, Jennifer M.; MacFarland, Suzanne P.; Das, Anirban; et al. (Clinical cancer research, 2025)
Schwannomatosis (SWN) is a distinct cancer predisposition syndrome caused by germline pathogenic variants in the genes NF2, SMARCB1, or LZTR1. There is a significant clinical overlap between these syndromes with the hallmark of increased risk for cranial, spinal, and peripheral schwannomas. Neurofibromatosis type 2 was recently renamed as NF2-related SWN and is the most common SWN syndrome, with increased risk for bilateral vestibular schwannomas, intradermal schwannomas, meningiomas, and less commonly, ependymoma. SMARCB1-related SWN is a familial SWN syndrome associated with peripheral and spinal schwannomas and an increased risk for meningiomas and malignant peripheral nerve sheath tumors, even in the absence of radiation. These individuals do not develop bilateral vestibular schwannomas. Finally, patients with LZTR1-related SWN typically present with peripheral schwannomas, and unilateral vestibular schwannomas have been reported. The following perspective is intended to highlight the clinical presentation and international tumor surveillance recommendations across these SWN syndromes.